Genome-wide prediction methods for detecting genetic effects of donor chromosome segments in introgression populations - Falke, Karen Christin; Mahone, Gregory S.; Bauer, Eva; Haseneyer, Grit; Miedaner, Thomas; Breuer, Frank; Frisch, Matthias; Justus Liebig University Giessen (My University, 2014)
BACKGROUND:Introgression populations are used to make the genetic variation of unadapted germplasm or wild relatives of crops available for plant breeding. They consist of introgression lines that carry small chromosome segments from an exotic donor in the genetic background of an elite line. The goal of our study was to investigate the detection of favorable donor chromosome segments in introgression lines with statistical methods developed for genome-wide prediction. RESULTS:Computer simulations showed that genome-wide prediction employing heteroscedastic marker variances had a greater power and a lower false positive rate compared with homoscedastic marker variances when the phenotypic difference between the donor and recipient lines was controlled by few genes. The simulations helped to interpret the analyses of glycosinolate and linolenic acid content in a rapeseed introgression population and plant height in a rye introgression population. These analyses support the superiority of genome-wide prediction approaches that use heteroscedastic marker variances. CONCLUSIONS:We conclude that genome-wide prediction methods in combination with permutation tests can be employed for analysis of introgression populations. They are particularly useful when introgression lines carry several donor segments or when the donor segments of different introgression lines are overlapping.
Keywords: ddc:630